Developing Bilingual guidebook for Wonocoyo Tourism Village, Trenggalek - Wahyuningtyas, Dwi; Nuryananda, Praja Firdaus; Masayu, Revina Dwi; Ajinegoro, Brian Tyan Mukti; Trirahardjo, Muhammad Rizqy; Sulistyo, Nanda (Journal of Community Service and Empowerment, 2026)
Located at Taman Kili-kili Beach, Wonocoyo Village, Panggul District, Trenggalek Regency, the PKM (Community Service) Education team of UPN Veteran East Java successfully held a tour guide training program and developed a bilingual guidebook in English and Indonesian on June 28, 2024. The training was attended by the Head of the Tourism and Culture Office of Trenggalek Regency, Drs. Sunyoto, and involved approximately 30 participants from Wonocoyo Tourism Village and Nglebeng Tourism Village. Wonocoyo Tourism Village is renowned for its natural attractions, including Kili-kili Park (a turtle hatchery), Pelang Beach, and its waterfall. Meanwhile, Nglebeng Tourism Village is known for the increasingly popular Kuyon Beach, located near rice fields and rows of fishing boats. With their promising potential, both villages are being developed as leading sustainable tourism destinations in Trenggalek, East Java, and potentially at the international level. To support this goal, the availability of bilingual guidebooks and trained tour guides is essential. The program contributes directly to SDG 4.4, by enhancing relevant skills for employment in the tourism sector, and to SDG 8.9, by promoting sustainable tourism that creates jobs and showcases local culture and nature. This initiative also supports community empowerment by equipping local residents with knowledge, communication skills, and tools to independently promote their tourism assets. The bilingual guidebook is expected to aid tour guides and tourism actors in effectively communicating the unique tourism potential of Wonocoyo and Nglebeng Villages to both domestic and international visitors.